Development and implementation of an online clinical pathway for adult chronic kidney disease in primary care: a mixed methods study. Issue 1 (December 2016) - Donald, Maoliosa; McBrien, Kerry; Jackson, Wes; Manns, Braden; Tonelli, Marcello; King-Shier, Kathryn; Jindal, Kailash; Lewanczuk, Richard; Scott-Douglas, Nairne; Braun, Ted; Straus, Sharon; Naugler, Christopher; et al.
Abstract Background Primary care physicians and other primary health care professionals from Alberta, Canada identified a clinical pathway as a potential tool to facilitate uptake of clinical practice guidelines for the diagnosis, management and referral of adults with chronic kidney disease. We describe the development and implementation of a chronic kidney disease clinical pathway (CKD-CP;www.ckdpathway.ca ). Methods The CKD-CP was developed and implemented based on the principles of the Knowledge-To-Action Cycle framework. We used a mixed methods approach to identify the usability and feasibility of the CKD-CP. This included individual interviews, an online survey and website analytics, to gather data on barriers and facilitators to use, perceived usefulness and characteristics of users. Results are reported using conventional qualitative content analysis and descriptive statistics. Results Eighteen individual interviews were conducted with primary care physicians, nephrologists, pharmacists and nurse practitioners to identify themes reflecting both barriers and facilitators to integrating the CKD-CP into clinical practice. Themes identified included: communication, work efficiency and confidence. Of the 159 participants that completed the online survey, the majority (52 %) were first time CKD-CP users. Among those who had previously used the CKD-CP, 94 % agreed or strongly agreed that the pathway was user friendly, provided useful information and increased their knowledge and confidence in the care of patients with CKD. Between November 2014 and July 2015, the CKD-CP website had 10, 710 visits, 67 % of which were new visitors. The 3 most frequently visited web pages werehome, diagnose andmedical management . Canada, Indonesia and the United States were the top 3 countries accessing the website during the 9 month period. Conclusions An interactive, online, point-of-care tool for primary care providers can be developed and implemented to assist in the care of patients with CKD. Our findings are important for making refinements to the CKD –CP website via ongoing discussions with end-users and the development team, along with continued dissemination using multiple strategies.